CODE MIXING AS LANGUAGE STYLE IN COMMUNICATION THROUGH SOCIAL MEDIA TWITTER - Putu Ega Meliani; Ni Made Ratminingsih; Gede Mahendrayana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This paper aims to recognize the types of code-mixing and factors influencing code-mixing byTwitter users. This study uses a descriptive qualitative research design. The subject of this study isTwitter users who post tweets that contained code-mixing. The researcher uses documentation andinterview as data collection methods. The data for identifying the types of code-mixing were collectedby documenting the tweets posted previously by Twitter users on the Twitter platform. The interviewguide was used to ask questions to respondents about the factors influencing the use of code-mixingin communication as language style. The data were analyzed through three stages: data reduction,data display, and conclusion: verifying. The data collected from documentation and interviewshowed that insertion code-mixing became the dominant type used among Twitter users. It isinfluenced by several factors from within of language speaker and external factors.